Characterization of the complete plastome sequence of Asplenium ×bimixtum (Aspleniaceae). Issue 2 (2nd April 2020) - Ha, Young-Ho; Gil, Hee-Young; Kim, Dong-Kap
Abstract: The complete plastome sequence of Asplenium × bimixtum (Aspleniaceae) was determined. The whole genome is 153, 098 bp in length, consisting of large (86, 394 bp) and small (21, 508 bp) single-copy regions, and a pair of identical inverted repeats (22, 598 bp). The genome contains 88 protein-coding genes, 33 tRNA genes, 8 rRNA genes, and 1 pseudogene ( infA ). The phylogenetic analysis based on 84 protein-coding genes showed that Asplenium is monophyletic with high bootstrap value.